APPLICATION OF TAX PLANNING TO THE FIXED ASSET DEPRECIATION METHOD AT PT. PERKEBUNAN III - Irananda Sihombing; Indah Cahya Sagala; Thezar Fiqih Hidayat Hasibuan (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
This research analyzes the impact of implementing tax planning on the fixed asset depreciation methods within PTPN III. The main objective of this study is to identify how the implementation of tax planning strategies affects the choice of fixed asset depreciation methods within PTPN III. The research method employed is a quantitative approach, collecting data through in-depth interviews with relevant stakeholders at PTPN III and analyzing documents related to the depreciation policies and the company's tax planning strategies. The results of this research show that by incorporating the straight-line depreciation method (tax) into its fixed asset depreciation, with a total accumulated depreciation smaller than declining balance (tax), PTPN III has saved on taxes, thus achieving its tax planning objectives.